Structure and dynamics of nano-sized raft-like domains on the plasma membrane - Herrera, Fernando Enrique (2012)
Cell membranes are constitutively composed of thousands of different lipidic species, whose specific organization leads to functional heterogeneities. In particular, sphingolipids, cholesterol and some proteins associate among them to form stable nanoscale domains involved in recognition, signaling, membrane trafficking, etc. Atomic-detail information in the nanometersecond scale is still elusive to experimental techniques. In this context, molecular simulations on membrane systems have provided useful insights contributing to bridge this gap. Here we present the results of a series of simulations of biomembranes representing non-raft and raft-like nano-sized domains in order to analyze the particular structural and dynamical properties of these domains. Our results indicate that the smallest (5 nm) raft domains are able to preserve their distinctive structural and dynamical features, such as an increased thickness, higher ordering, lower lateral diffusion, and specific lipid-ion interactions. The insertion of a transmembrane protein helix into non-raft, extended raft-like, and raft-like nanodomain environments result in markedly different protein orientations, highlighting the interplay between the lipid-lipid and lipid-protein interactions. © 2012 American Institute of Physics.